The Effect Of Customer Experience, Customer Satisfaction And Word Of Mouth On Customer Loyalty - Roza Aulia Abidin; Yuyus Yudistria; Abdul Haeba Ramli (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to analyze the effect of customer experience, customer satisfaction and word of mouth on customer loyalty. This research uses quantitative methods, with data collection techniques in the form of surveys by distributing questionnaires to respondents online. Data analysis method using Statistical Product and Service Solutions (SPSS). The research findings show that customer experience, word of mouth have a significant effect on customer loyalty, while customer satisfaction does not show a significant impact. And customer experience, customer satisfaction, word of mouth together have an effect on customer loyalty. These study emphasizes the importance of the influence of customer loyalty on spotify premium customers who are loyal to keep using a product or service in the long term. The result of the managerial implications is important factors need to be improved by customer loyalty from using spotify premium, consistent user experience and ensuring that the spotify app offers a good and consistent user experience across devices and platforms. Improve the recommendation algorithm to offer more relevant and personalized suggestions for each user. Provide fast and effective customer service to help users resolve technical issues   Keywords: Customer Experience, Customer Satisfaction, Word of Mouth, Customer Loyalty